Sintesis dan Karakterisasi Katalis Aluminosilikat dari Kaolin - Zafirah, Shakanti 'Aqilah; Windhy Mutiara Salsabillah; Sintha Soraya Santi; Nurul Widji Triana; Susilowati (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study aims to synthesize and characterize aluminosilicate catalysts derived from Indonesian kaolin through the hydrothermal method with variations in surfactant type and aging temperature. Kaolin served as the main source of silica and alumina, while CTABr (cationic) and PEG (non-ionic) acted as structure-directing agents that guided the formation of the catalyst pore framework. The synthesis was carried out at aging temperatures of 25°C, 40°C, 50°C, 65°C, and 70°C to investigate their effects on the functional groups and crystallinity of the catalysts. FTIR analysis revealed the presence of main Si–O–Si and Al–O–Si functional groups in all samples, with additional organic peaks attributed to the surfactants. Samples synthesized with CTABr showed sharper spectral peaks, indicating a more ordered structure. XRD analysis showed that the aluminosilicate catalyst synthesized with CTABr at 50°C exhibited the highest diffraction intensity (2615 cts), representing higher crystallinity compared to the PEG-based sample, which remained amorphous. SEM observations demonstrated that PEG produced smoother and more porous particle morphology, while CTABr resulted in agglomerated particles. Overall, the combination of CTABr surfactant and 50°C aging temperature yielded the best synthesis result with a stable semi-crystalline structure. This research highlights the great potential of local kaolin as a sustainable and efficient raw material for aluminosilicate catalyst production.